Collaborative Projects : an Interdisciplinary Study. - Blunden, Andy (Studies in critical social sciences, 2014)
Collaborative Projects - An Interdisciplinary Study demonstrates that the concept of 'project' may unify research across a range of human sciences, and presents eleven diverse research projects and a philosophical introduction to prove it.